Evaluation of Human Resource Information System by Using HOT-Fit Model - Nindya Agustin Widiastuti; Sri Gunani Partiwi (Institut Teknologi Sepuluh Nopember, 2020)
Today’s competitive business environment, many organization give more attention to enhance effectiveness and efficiency of employee. PT Pembangkitan Jawa Bali as a subsidiary of PT PLN (Persero) also continues to improve business processes of Human Resource Management through the application of Human Resource Information System (HRIS). This application has been developed since 2016 and is still implemented 67% of the HRIS PJB model design. This certainly raises questions about the development of HRIS PJB implementation, which is need for an evaluation of the implementation of HRIS PJB applications. HRIS Manager has never conducted an evaluation of HRIS PJB that can strengthen the benefits of its use for employees. Therefore, this study was conducted to evaluate the use of HRIS PJB applications in this case the focus on the Personal Management module in order to assess its usefulness to the needs of users and organizations by using Human Organization Technology (HOT) Fit Model. Primary data were obtained through a survey method by distributing questionnaires to PT PJB employees as application users. Data analysis method used is Partial Least Square using SmartPLS. The results of this study shows the suitability of this application benefits. If there is a gap, alternative solutions are needed to improve and develop applications in the future. Decision making through Borda Count Method is used to get the right solution with the current conditions and can be used as improvements priority and development of HRIS PJB applications for both application managers and management of PT PJB.